Water Hybrid System to Run Vehicles on Water (International Journal of Current Engineering and Technology, 2014)
Who says cars cannot run on water? The paper focuses to develop practical and efficient technique to make cars run on water. The water‐hybrid system is a practical solution developed for use in fuel‐injected and carbureted motor vehicles. The secret of the water‐hybrid system lies within its HyTronic module. It produced relatively low voltage, but uniquely shaped electronic pulses of precise frequency and duration. The overall power consumption of the HyTronic module and the entire water‐hybrid system is fairly low; actually low enough to be easily powered by your vehicle excess electrical and heat output, and with enough reserve power left to help run all your vehicle’s other electrical devices. You don’t need carbon that pollutes atmosphere and bankrupt citizens.
Keywords: Water Hybrid System; HyTronic module etc.